Facets, features and forms of firm-level innovation in the agribusiness sector of sri lanka - Abeykoon, K.S.L.; Ikram, S.M.M.; Jayasinghe Mudalige, U.K.; Edirisinghe, J.C.; Dissanayake, S.N. (University of Jaffna, 2012)
As for any enterprise, innovation is considered as one of the most important factors to enhance competitiveness of agribusiness firms in both national and international markets. The managerial requirement of creating, shaping, and managing innovation, however, cannot be fulfilled without an understanding of forms and processes of innovation that is in practice within these enterprises. The fact in extant literature remains that the specific role of innovation in the context of the agribusiness sector in Sri Lanka is not yet fully explored. In this shed of light, the specific objective of this study was to undertake a qualitative exploration of various facets of firm-level innovation in Sri Lankan agribusiness sector with a focus of selected key sub-sectors, including: agricultural inputs, processed fruits/vegetables, plantation products, dairy products, meat/fish processing, diversified agribusinesses, which have been deemed excellent in performance over the years. In-depth face-to-face interviews with a senior manager of ten companies selected for the purpose were carried out with a support of a structured interview schedule. The interviews were voice recorded, transcribed and analyzed using N-Vivo (version 7.0) software package to derive underlying insights and isolate cognitive factors that pertain to innovation within these firms. Using the node development tools in N-Vivo, data were coded to create distinct labels within three broad categories, including: type of innovation, internal dimensions, and external context. Two forms of innovation were identified such as an incremental innovation of their existing product lines and innovations that lead to productivity and process improvements. In addition, these companies believe in the marketing of value added products as a form of innovation. Adoption and implementation of quality processes and systems was accentuated as an important element of organizational innovativeness. Furthermore, links with external institutions and quality of human capital were highlighted as important factors determining the innovation drive of these organizations. Interestingly there were no substantial indications in the results for firms being engaged greatly in other forms of innovation as exemplified in management/organizational behavior literature such as strategic, administrative and marketing innovation.
Keywords: Agribusiness sector; Innovation; Qualitative data analysis